INTEGRATING CONTEXTUAL LEARNING AND TRADITIONAL GAMES: DEVELOPMENT OF ADVENTURE BOARD GAME AS MEDIA FOR IPAS - mauliseee meaa (CV Grasta Glory, 2026)
IPAS learning in elementary schools requires contextual and interactive learning media to support students’ active engagement and meaningful understanding of scientific and social concepts. However, classroom learning is often dominated by textbook use and teacher-centered instruction, which limits students’ motivation and participation. This study aims to develop a contextual-based Adventure Board Game learning media for the IPAS subject in Grade IV elementary school. The research method used was Research and Development (R&D) with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were nine Grade IV students of SD Negeri Napallicin, North Musi Rawas Regency. Data collection techniques included observation, interviews, expert validation sheets, teacher and student questionnaires, and learning outcome tests. The results show that the developed learning media obtained a validity score of 0.87, categorized as very valid. The practicality assessment results indicate an average score of 89.33%, categorized as very practical. Meanwhile, the effectiveness test results show an average score of 83%, categorized as very effective. Based on these findings, the contextual-based Adventure Board Game learning media is suitable for use in IPAS learning in Grade IV elementary school. This study implies that integrating traditional games into contextual learning can enhance students’ engagement and learning outcomes. Future research is recommended to implement the developed media on a larger scale and explore its application in other subjects and grade levels.